DESKRIPSI PEMANFAATAN LIMBAH INDUSTRI SAWIT DI PT. FAJAR SAUDARA KUSUMA DESA SEBAWI KABUPATEN SAMBAS - Jannah, Miftahul; Buwono, Sri; Anasi, Putri Tipa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The objective of this research determine the utilization of waste from palm oil processing at PT. Fajar Saudara Kusuma in Sebawi Village,Sebawi Sub-District, Sambas Regency, West Kalimantan, Indonesia. The research method used in this study is the traditional case styudy method. The data collection technique in this study used a triangulation technique, which is a combination of observation, interview and documentation techniques. The data collect with laptop and observation sheets, cameras and interview guidelines. Data analysis wear the Miles and Huberman design which be composed of data reduction, data presentment, and inference drawing. The out put showed that (1) the utilization of the waste used was in the form of solid waste and liquid waste, the solid waste used were shells, empty leaves and fibers, while the liquid waste itself was liquid waste originating from palm oil processing. (2) the form of utilization of palm oil fibers and shells is used as fuel for steam boilers as a resource of electrical force for the palm oil processing process at PT. Fajar Saudara Kusuma, while the empty leaves used as soil fertilizer and processed to form ash. Liquid waste is used as soil fertilizer for oil palm plantations in the company's plantations.